(untitled) (Journal of Nepal Geological Society, 2016)
Rivers have always been an indispensable part of the human civilization. They play a vital role in daily life purposes to big engineering constructions such as dams, reservoirs or hydropower projects. It is mandatory to understand the morphology and dynamics of the river before initiating any projects for easier planning and to prevent possible damage to structures. The Malekhu Khola area is one of the potential areas for urbanization and has already been undergoing development of settlement and other infrastructures. This paper describes the morphology and dynamics of the Malekhu Khola to classify and characterize the river’s behavior and competency. The Malekhu Khola is a sixth-order river having its total length of 24.83 km, watershed area of 101.28 km2 and the average gradient of 0.041 m/m. Various morphological parameters were measured with the aid of topographic maps, aerial photographs and Geographic Information System (GIS). The hydraulic parameters, channel sediment and slopes were measured at 10 different transects sites through field surveys. The river was classified using the Rosgen’s Level II criteria. The river reaches have been classified as A4-, B4- and C4-type streams. A4- and B4-type streams are moderate-gradient gravelly and low sinuosity rivers whereas C4-type streams are low-gradient gravelly meandering river. The Malekhu Khola gradually changes from A4- to B4-type streams up to 12 km downstream, and then to C4-type stream further downstream, but B4-type streams reappear within the distance of 15 km to 19 km from the origin. This study presents temporal changes in river channel, and flow competence and aggrading/degrading potential evaluation of the Malekhu Khola.